ECONOMIC IMPACT ANALYSIS OF APT PRANOTO AIRPORT PROJECT DURING CONSTRUCTION PHASE - Adisthy Shabrina Nurqamarani; Faizal Reza (Faculty of Economics and Business, University of Pasundan, 2019)
The aim of this research was to provide the evidence of economic benefits resulted from development of APT Pranoto airport towards East Kalimantan which will strengthen the support of the development of the new airport from various stakeholders. This research applied input-output, analysis to estimate the economic impact i.e impact of expenditure on construction phase. Direct impact includes the increase in gross value added as well as income from tax payment and create new employment. Indirect impact includes increase in capital spending of the workers and more money circulated within the area of East Kalimantan. This study conclude that there are direct and indirect impacts from APT Pranoto airport during construction phase within the period of 5 years. The findings can be used to emphasize APT Pranoto Airport Project in gaining funding and acceptance from local economy.